2017
DOI: 10.1002/jts.22235
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and Somatic Complaints in a Deployed Cohort of Georgian Military Personnel: Mediating Effect of Depression and Anxiety

Abstract: Several studies have shown the relationship between symptoms of posttraumatic stress disorder (PTSD), somatic symptoms, and the mediating effect of depression and anxiety. The following study was conducted to investigate the relationship between PTSD symptoms and somatic complaints through underlying symptoms of depression and anxiety. The participants of the study were 2,799 veterans who were examined after a 6-month deployment. They were assessed using the PTSD Checklist (PCL-5) and Patient Health Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
(96 reference statements)
0
6
0
1
Order By: Relevance
“…As previously discussed, these are the symptoms to target initially to reduce PTSD and suicidality. 63,64 Generalized anxiety is an area to consider because it was positively significantly related to all the factors. Researchers found that anxiety contributed to suicide risk among FFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously discussed, these are the symptoms to target initially to reduce PTSD and suicidality. 63,64 Generalized anxiety is an area to consider because it was positively significantly related to all the factors. Researchers found that anxiety contributed to suicide risk among FFs.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, it should be an alert to practitioners that individuals reporting somatic symptoms might have affective depression. As previously discussed, these are the symptoms to target initially to reduce PTSD and suicidality 63,64 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with findings from prior studies in the literature, including a study among veterans with PTSD which found that many felt as though they lacked “emotional readiness” for treatment, and that engaging in care would increase anxiety levels [ 39 ]. Many participants also reported experiencing somatic symptoms, a well-established comorbidity of PTSD [ 41 ]. Avoidance of trauma-related stimuli is a hallmark feature of post-traumatic stress disorder, for which 93% of women in our study potentially met criteria [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in certain populations of military personnel, perceptions of general disapproval in society were largely correlated with both PTSD symptoms and depression. In addition, the physiological impact of bodily injury, positively correlated with PTSD, further complicates treatment (Giordano, Bader, Richmond, & Polomano, 2018; Sikharulidze et al, 2017). Attempts to integrate traumatic experiences with previously established assumptions about the self and the world can be met with guilt, anger, and rumination because these discrepancies are not often easily resolved and can result in varied structural changes to personality (Brewin, 2011).…”
mentioning
confidence: 99%